7T MRI in natalizumab-associated PML and ongoing MS disease activity: A case study. Issue 6 (December 2015) - Sinnecker, Tim; Othman, Jalal; Kühl, Marc; Mekle, Ralf; Selbig, Inga; Niendorf, Thoralf; Kunkel, Annett; Wienecke, Peter; Kern, Peter; Paul, Friedemann; Faiss, Juergen; Wuerfel, Jens
Abstract : Objective: To assess the ability of ultra-high-field MRI to distinguish early progressive multifocal leukoencephalopathy (PML) from multiple sclerosis (MS) lesions in a rare case of simultaneous presentation of natalizumab–associated PML and ongoing MS activity. Methods: Advanced neuroimaging including 1.5T, 3T, and 7T MRI with a spatial resolution of up to 0.08 mm 3 was performed. Results: 7T MRI differentiated between PML-related and MS-related brain damage in vivo. Ring-enhancing MS plaques displayed a central vein, whereas confluent PML lesions were preceded by punctate or milky way–like T2 lesions. Conclusions: Given the importance of early diagnosis of treatment-associated PML, future systematic studies are warranted to assess the value of highly resolving MRI in differentiating between early PML- and MS-induced brain parenchymal lesions.